Planar integration of flexible micro-supercapacitors with ultrafast charge and discharge based on interdigital nanoporous gold electrodes on a chip. Issue 24 (1st June 2016) - Zhang, Chao; Xiao, Jian; Qian, Lihua; Yuan, Songliu; Wang, Shuai; Lei, Pengxiang
Abstract : A flexible micro-supercapacitor based on interdigital nanoporous gold electrodes is elaborately designed through direct writing technology, exhibiting excellent electrochemical performance. Abstract : Flexible, wearable, implantable and easily reconfigurable micro-fabricated pseudocapacitors with impressive volumetric stack capacitance and energy densities are desired for electronic devices. In this work, scratching technology at the micron-scale enables construction of the planar electrode systems directly based on nanoporous gold films. We demonstrate that both nanoporous channels with high ion-accessible ability and interconnected skeletons with high conductivity enable the design of pseudocapacitive micro-supercapacitors with high performances. These planar devices show several attractive features including ultrafast charge/discharge (high rate), large capacitance (1.27 mF cm −2, 127 F cm −3 ), and ultrahigh energy density (0.045 W h cm −3 ) while maintaining a high power density (22.21 W cm −3 ). Especially, the superb cyclability and mechanical flexibility give them great potential for future microelectronics with a tiny volume. The design concept reported here provides an avenue to integrate planar micro-supercapacitors into large-scale devices with a small environmental footprint.